Use of vocabulary activities and their impact in the reading comprehension skills of students of fifth grade (2018)
This paper displays the procedure and outcomes of an investigation process resulting from the identification of a class issue detected while the development of my pedagogical practice. An action research was conducted in order to identify the impact of vocabulary activities in the development of reading comprehension skills in students of fifth grade at a public school in Bucaramanga, by following a task-based teaching methodology for the pedagogical intervention and the principles of a qualitative research for the investigation design. In addition, this thesis examines the results according the guide of H. O'Connor and N. Gibson for data analysis being possible to identify several interesting conclusions regarding students’ response time, behavior and interest towards reading; information that become in useful material to be considered to foster pedagogical practices and enhance student’s learning outcomes when teaching EFL.